Prevalence of Pregnant Women with Anemia in Sangkan Gunung Village, Karangasem Regency, Bali-Indonesia - Luh Seri Ani; Ketut Suwiyoga (Journal of Global Pharma Technology, 2017)
Pregnant women are one of the groups with the risk of having anemia. Some factors that are correlated to anemia is an infectious disease, bleeding, and low iron daily intake.These factors were related to the knowledge level of pregnant women and iron supplementation compliance. This is a cross-sectional study with descriptive methods, where 34 pregnant women were chosen by consecutive sampling method. Anemia was then measured by sahli method, and hemoglobin level < 11 g/dl were categories as anemia. The results were analyzed with univariate and bivariate analysis using SPSS 23. Anemia in pregnant women at Sangkan Gunung village, Sidemen sub-district is20,6%.  Most anemia incidents were found in 20-35 years old pregnant women, with low education level, work at the office, zero parity, and in afirst trimester. Anemia was not associated with chronic energy deficiency, knowledge level and iron supplementation compliance level (P>0,05). Anemia prevalence of pregnant women was relatively low, but the preventive effort must be taken to decrease therate of anemia prevalence.Keywords: Knowledge, Compliance, Iron tablets, Pregnant women, Anemia.